Porous macromolecular dihydropyridyl frameworks exhibiting catalytic and halochromic activity - Xiao, Bo; Easun, Timothy L.; Dhakshinamoorthy, Amarajothi; Cebula, Izabela; Beton, Peter H.; Titman, Jeremy J.; Garcia, Hermenegildo; Thomas, K. Mark; Schröder, Martin (Royal Society of Chemistry, 2014)
New porous macromolecular frameworks (PMFs) have been designed and prepared by the condensation of dialdehydes with aminoacrylonitriles. Two porous materials were prepared by reacting 3,3′-benzene-1,4-diylbis(3-aminoprop-2-enenitrile) with benzene-1,4-dicarbaldehyde and biphenyl-4,4′-dicarbaldehyde to give PMF-NOTT-1 and PMF-NOTT-2, respectively. Adsorption and desorption studies of N2 (77 K) and CO2 (273–303 K and 20 bar) were used to characterize the porosity of these materials. CO2 adsorption measurements indicate that these PMFs have similar porosity with Dubinin–Radushkevich micropore volumes of 0.142 and 0.144 cm3 g−1 and CO2 surface excess uptakes of 28.4 and 28.9 wt% at 20 bar, 273 K for PMF-NOTT-1 and PMF-NOTT-2, respectively. The isosteric heats of adsorption for CO2 at zero surface coverage were 31.9 kJ mol−1 (for PMF-NOTT-1) and 33.1 kJ mol−1 (for PMF-NOTT-2). However, N2 adsorption studies at 77 K indicated that PMF-NOTT-2 shows activated diffusion effects due to the presence of some narrow ultramicroporosity. The conjugated systems of these frameworks can be reversibly switched by varying proton concentration in solution and these materials thus demonstrate halochromic properties. PMF-NOTT-1, constructed from shorter building blocks than PMF-NOTT-2, exhibits higher catalytic activity and selectivity in Knoevenagel condensation reactions of malononitrile with benzaldehydes. The advantages of using PMFs as catalysts or adsorbents are their excellent thermal and chemical stabilities and they can be recovered and regenerated for re-use.